The Art of Translating Indonesian Folklore: A Case Study of “Hasil Sebuah Kejujuran” by Bambang Subagyo” - Latranita, Elsa; Sembiring, Milisi; sitinjak, Vivi Novalia (English Lecturers and Teachers Association (ELTA), 2024)
This study used translation techniques to translate the source language into the target language and analyzed cultural terms in translating the Indonesian folklore